2015
DOI: 10.1103/physreve.91.042904
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of the localization measure in a finite-dimensional model of the quantum kicked rotator

Abstract: We study the quantum kicked rotator in the classically fully chaotic regime K = 10 and for various values of the quantum parameter k using Izrailev's N -dimensional model for various N ≤ 3000, which in the limit N → ∞ tends to the exact quantized kicked rotator. By numerically calculating the eigenfunctions in the basis of the angular momentum we find that the localization length L for fixed parameter values has a certain distribution, in fact its inverse is Gaussian distributed, in analogy and in connection w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…For details see reference [52]. Nevertheless, one should observe some scattering of points around the mean value, noted already by Izrailev [35] in the case of the quantum kicked rotator, which probably is due to the fact that the localization measure has a certain distribution rather than a sharp value, as has been observed recently in the kicked rotator by Manos and Robnik [71].…”
Section: The Localization Measures: a C And Niprsupporting
confidence: 51%
“…For details see reference [52]. Nevertheless, one should observe some scattering of points around the mean value, noted already by Izrailev [35] in the case of the quantum kicked rotator, which probably is due to the fact that the localization measure has a certain distribution rather than a sharp value, as has been observed recently in the kicked rotator by Manos and Robnik [71].…”
Section: The Localization Measures: a C And Niprsupporting
confidence: 51%
“…In both cases the scattering of points around the mean linear behaviour is significant, and it is related to the fact that the local- ization measure A of eigenstates has some distribution P (A), as observed and discussed in Ref. [39] for the quantum kicked rotator, and discussed for the stadium billiard in the previous section IV.…”
Section: Implications Of Localization For the Spectral Statisticsmentioning
confidence: 62%
“…[12] it has been demonstrated that β is a unique function of A in the billiard with the mixed phase space [13,14], but is not linear. Finally, Manos and Robnik [39], have observed that the localization measure in the quantum kicked rotator has a nearly Gaussian distribution, and this was a motivation for the work in the present paper, where we study the distributions of A in the stadium billiard, systematically in almost all regions of interest (determined by the shape parameter ε and the energy), and also the dependence of its standard deviation on the control parameter α, while the dependence of < A > on α as an empirical rational function is already known from our previous paper [16].…”
Section: Introductionmentioning
confidence: 96%
“…It was mainly Izrailev who has studied the relation between the spectral fluctuation properties of the quasienergies (eigenphases) of the quantum kicked rotator and the localization properties [14][15][16]. This picture has been recently extended in [17][18][19][20] and is typical for chaotic time-periodic (Floquet) systems. Similar analysis in the case of the stadium as a time independent system is in progress [21].…”
Section: Introductionmentioning
confidence: 99%